Some Subspaces of Generalized Entire Sequences of Fuzzy Numbers (Journal of Informatics and Mathematical Sciences, 2011)
The object of the present paper is to introduce the sequence spaces $λ_{0} (F, p)$ defined by the sequence of fuzzy numbers and $p=(p_{k})$ be any bounded sequence of positive real numbers. We study their different algebraic and topological properties. We also obtain some inclusion relations between these spaces.
Keywords: Fuzzy number; Entire sequence spaces; Completeness; Bounded sequence; Cauchy sequence